The Use of Subtitled Video Animation To Improve Students Vocabulary At Ban Erawan School Thailand - Diana Fitri; Ulfatul Ma’rifah (Universitas Negeri Semarang, 2022)
The purpose of this research is to examine how students utilize animated video subtitles to increase their English vocabulary and reading comprehension. This study used a quantitative experimental design using class VI research participants. The participants in this research were all Ban Erawan School pupils, a total of 32 persons. The three steps of data collecting are pre-test, treatment, and post-test. The data from this research will be evaluated to see whether the experimental and control groups yield substantially different outcomes. The experimental class received animated movies with captions, but the control class did not. Initially, pupils in both grades received a pre-test. The experimental class was then given therapy, and the pupils completed the post-test. The study of the collected data results in the following conclusions: 1) Animated video media with subtitles has a considerable influence on pupils' English vocabulary and reading development. 2) Students' reading of animated films with subtitles receives a substantial score, precisely 0.05. 3) The difference in the average value of vocabulary learning outcomes for experimental class students is 77.18, whereas the control class is 55.62. while the results of learning to read experimental class students as much as 71.87 for the control class as much as 62.81. The conclusion that animated video media with subtitles has a significant increase in the vocabulary mastery of elementary school students is reached based on the data examination conducted.